Psychological Resilience in Human-AI Relationships: A Reading of Ian McEwan’s Machines Like Me - R.Gayatri; Dr P. Lalitha (ILN Journal: Indian Literary Narratives, 2025)
Resilience is usually characterized in psychology as an individual's capacity to withstand adversity and recuperate from trauma. Nevertheless, the emergence of advanced artificial intelligence necessitates a reevaluation of this notion. This research analyzes Ian McEwan’s Machines Like Me to investigate how resilience manifests as both a personal characteristic and a relational, developmental phenomenon influenced by human–AI interactions. This study employs established psychological theories of resilience and a detailed textual analysis of McEwan’s story to position resilience as a dynamic construct that develops through reciprocal adaptation, emotional connection, and ethical negotiation between humans and machines.The study examines critical interactions among Charlie, Miranda, and Adam, illustrating how resilience is redefined within the framework of relational interdependence, collective ethical issues, and shifting identities. Research indicates that McEwan’s novel depicts resilience as an adaptive, transformational process rather than a static personal trait, emerging from the co-construction of meaning and emotional symbiosis between humans and AI. This reframing underscores the necessity of expanding psychological and literary understandings of resilience to include human–technology relationships, ultimately illustrating that resilience in the age of AI is not solely individualistic but relational, ethical, and identity-forming.